Determinants of survival in myelofibrosis patients undergoing allogeneic hematopoietic cell transplantation - Hernández-Boluda, Juan Carlos; Pereira, Arturo; Kröger, Nicolaus; Beelen, Dietrich; Robin, Marie; Bornhäuser, Martin; Angelucci, Emanuele; Vitek, Antonin; Blau, Igor Wolfgang; Niittyvuopio, Riitta; Finke, Jürgen; Cornelissen, Jan J.; et al. (Leukemia, 2021)
We aimed to evaluate the determinants of survival in myelofibrosis patients undergoing allogeneic hematopoietic cell transplantation (allo-HCT) and to describe factors predicting the main post-HCT complications. This retrospective study by the European Society for Blood and Marrow Transplantation included 2916 myelofibrosis patients who underwent first allo-HCT from an HLA-identical sibling or unrelated donor between 2000 and 2016. After a median follow-up of 4.7 years from transplant, projected median survival of the series was 5.3 years. Factors independently associated with increased mortality were age ≥ 60 years and Karnofsky Performance Status <90% at transplant, and occurrence of graft failure, grades III–IV acute graft-vs.-host disease (aGVHD), and disease progression/relapse during follow-up. The opposing effects of chronic graft-vs.-host disease (GVHD) on non-relapse mortality and relapse incidence resulted in a neutral influence on survival. Graft failure increased in unrelated donor recipients and decreased with myeloablative conditioning (MAC) and negative donor/recipient cytomegalovirus serostatus. Risk of grades III–IV aGVHD was higher with unrelated donors and decreased with MAC. Relapse incidence tended to be higher in patients with intermediate-2/high-risk DIPSS categories and to decrease in CALR -mutated patients. Acute and chronic GVHD reduced the subsequent risk of relapse. This information has potential implications for patient counseling and clinical decision-making.